2015
DOI: 10.1371/journal.pone.0132640
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of the PNPLA3 rs738409 Polymorphism on Non-Alcoholic Fatty Liver Disease and Renal Function among Normal Weight Subjects

Abstract: In normal weight subjects (body mass index < 25 kg/m2), non-alcoholic fatty liver disease (NAFLD) is likely to coexist with metabolic diseases. The patatin-like phospholipase 3 (PNPLA3) polymorphism rs738409 (c.444C>G) is associated with the risk of NAFLD and/or renal dysfunction; however, the influence of the weight status on the associations remains unknown. We aimed to clarify the associations of the PNPLA3 polymorphism with the risk of NAFLD and/or renal dysfunction, while also paying careful attention to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
73
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 37 publications
8
73
1
1
Order By: Relevance
“…Musso et al demonstrated in adults with and without NAFLD that the PNPLA3 148M allele was associated with lower eGFR levels. 18 Similarly, Oniki et al 19 The novel findings of the present study were that, in children with obesity, children with PNPLA3 MM genotype compared with those with either PNPLA3 IM or II genotypes showed lower eGFR levels both in the presence and absence of NAFLD. At GLM, however, the effect of PNPLA3 148M allele on eGFR was lost in patients without NAFLD demonstrating a poor effect of this allele on eGFR in the absence of NAFLD.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Musso et al demonstrated in adults with and without NAFLD that the PNPLA3 148M allele was associated with lower eGFR levels. 18 Similarly, Oniki et al 19 The novel findings of the present study were that, in children with obesity, children with PNPLA3 MM genotype compared with those with either PNPLA3 IM or II genotypes showed lower eGFR levels both in the presence and absence of NAFLD. At GLM, however, the effect of PNPLA3 148M allele on eGFR was lost in patients without NAFLD demonstrating a poor effect of this allele on eGFR in the absence of NAFLD.…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, Oniki et al demonstrated an effect of the PNPLA3 148M allele in declining eGFR in a population of 740 normal weight adults, and Mantovani et al found that regardless of the presence of NAFLD, in postmenopausal women with type 2 diabetes mellitus, the patients homozygous for the PNPLA3 rare allele had lower eGFR and higher prevalence of CKD.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported that an increase in bodyweight, triglyceride levels and PNPLA3 rs738409 were risk factors for the development of non‐obese NAFLD . In these reports, NAFLD was diagnosed by abdominal ultrasound or proton‐magnetic response spectroscopy, but our study performed liver biopsies in all NAFLD patients.…”
Section: Discussionmentioning
confidence: 92%
“…NAFLD. [37][38][39][40][41] In these reports, NAFLD was diagnosed by abdominal ultrasound or proton-magnetic response spectroscopy, but our study performed liver biopsies in all NAFLD patients. Our study indicated that bodyweight change, the presence of T2DM and rs738409 GG genotype were the risk factors for development of NAFLD in both non-obese and obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, NAFLD can also be observed in subjects with a normal‐weight (body mass index (BMI) <25 kg/m 2 ), especially in Asian populations . We recently reported that patatin‐like phospholipase domain‐containing 3 ( PNPLA3 ) rs738409, a well‐known polymorphism that predisposes carriers for a fatty liver, was associated with a risk of developing NAFLD, even in individuals with a normal weight status . Thus, the population background (e.g., genetic polymorphisms, lifestyle, age, gender, and underlying diseases) should be carefully considered when determining the association between the weight status and the risk of NAFLD; however, at present, no population models incorporating detailed population background information can predict this association with sufficient accuracy.…”
mentioning
confidence: 99%